The role of ergonomics issues in engineering education - Naeini, Hassan Sadeghi; Mosaddad, Seyyed Hashem (Elsevier, 2013)
Most of the engineers’ activities are related to workers and working process, therefore the majority of engineers have some sorts of communications with employees, directly or indirectly. Otherwise industrial hygiene and safety are known as an important issue for all of staffs, so the engineers need some appropriate information about occupational health. Undoubtedly, universities have an effective role to train the engineering students about human being and work related health and safety problems. One of the sciences which considers to human health, human performance and body activities is “Ergonomics”. In this study, the knowledge of the engineering students about ergonomics has been considered. In this regards, one of the well known technical universities in Iran with about five decades experience in offering engineering courses and programs was selected and 200 volunteer students among different disciplines (metallurgy, industrial Eng, mechanics, civil Eng., computer science, electrical and power Eng.) were interviewed in which their knowledge and awareness about ergonomics were questioned. The main focused point in an interview and questionnaire was ergonomics. This study showed that more than 71% of students did not have fair information about ergonomics and its importance in their future jobs. Also, statistical analysis by SpssWin showed a significant relationship between students with different disciplines in terms of their knowledge about ergonomics, however in this regards, there was no significant difference among students of industrial engineering who were in three different disciplines of industrial engineering. This case study emphasizes on offering a three-credit ergonomic course for all of the engineering students.